COMMUNITY SATISFACTION WITH MOTOR VEHICLE TAX PAYMENT SERVICES AT UNIT PELAKSANA TEKNIS DAERAH (UPTD) OF PENGELOLAAN PENDAPATAN DAERAH (PPD) SISTEM ADMINITRASI MANUNGGAL SATU ATAP (SAMSAT) TANJUNGPINANG - Nurhadiyanti Nurhadiyanti; Desrian Effendi; Endri Bagus Prasetiyo; Revy Dwiyustie Lianca; Anju Jumaran R (INDONESIAN GOVERNANCE JOURNAL : KAJIAN POLITIK-PEMERINTAHAN, 2024)
The purpose of this study is to measure the community satisfaction index and analyze the gap between service performance and community expectations. The 9 elements used based on the Regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform of the Republic of Indonesia Number 14 of 2017 consist of requirements, systems, mechanisms & procedures, completion time, costs / tariffs, product specifications type of service, executive competence, executive behavior, handling complaints, suggestions & input and infrastructure. This type of research is descriptive with a quantitative approach while the population of this study is two-wheeled and four-wheeled vehicle taxpayers in the working area of UPTD PPD SAMSAT Tanjungpinang which amounted to 68,977 taxpayers and the number of samples of this study used sample calculations developed by Morgan and Krejcie with a sample of 382 respondents. Then the data analysis technique uses the Community Satisfaction Index, Importance & Performance Analysis and gap analysis (GAP). The result of this study is a Community Satisfaction Index of 87.55 with service quality B. Measurement of service elements using cartesian diagrams there is 1 indicator in quadrant I (top priority), 13 indicators in quadrant II (maintain achievement), there are 7 indicators in quadrant III (low priority) and no indicators are included in quadrant IV (excessive). Then based on the GAP analysis, there are 8 indicators that are still below the average GAP score.